GAMBARAN PERSEPSI REMAJA PUTRI TENTANG BAHAYA PEROKOK PASIF TERHADAP FUNGSI REPRODUKSI WANITA DI SMAN 1 GALIS PAMEKASAN - Zhulvie Meylanzharie; Anis Nurlaili (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2021)
Cigarette smoke inhaled by passive smokers (not smoking) is as dangerous as cigarettes and smoke inhaled by active smokers (smoking). Therefore, the diseases suffered by passive smoking are almost the same as those suffered by active smokers. The impact of smoking on secondhand smoke can interfere with female reproductive functions such as cervical cancer, breast cancer, etc. The purpose of this study was to describe the perceptions of young women about the dangers of passive smoking on women's reproductive function. The research method used is descriptive. The study population was 315 girls at SMAN 1 Galis Pamekasan. The sample consisted of 176 people with stratified random sampling technique. The variable used is a single variable, namely the perception of young women. Data collection using a Likert scale questionnaire.The results showed that 176 adolescent girls (55.7%) had a positive perception of the dangers of passive smoking on female reproductive function.The conclusion of this study is that young women have positive perceptions about the dangers of passive smoking on female reproductive function. Efforts made are that young women are trying hard to avoid cigarette smoke, the school has made strict and strict rules about prohibiting smoking in the school environment by giving heavier sanctions such as calling parents of students, and the family making changes to smoking habits in the house, etc.